Appendiceal Hypoplasia - An Extremely Rare Appendiceal Anomaly - Deyab, Ashraf Abdelfatah; Abdalrahim, Salah Ahmed; Mohamed, Elsadig Yousif; Bashir, Atif Ali (IIUM Medical Journal Malaysia, 2018)
Appendiceal anomalies are extremely rare malformations that are usually found incidentally. Agenesis and duplication of the appendix has been well documented, however the reported cases of appendiceal hypoplasia are very limited, as only few cases have been reported so far. Here, we report a 31-year-old male who underwent appendicectomy after clinical presentation and diagnosis of appendicitis. The appendicular specimen showed all histomorphological features of appendiceal hypoplasia. Appendiceal hypoplasia is often missed and usually difficult to be diagnosed in the preoperative workup. The chief concern in this case is to focus on the classical histo-morphological features of appendiceal hypoplasia, especially in view of its clinical course.